Antígenos leucocitarios humanos y su asociación con resistencia/susceptibilidad a la infección por el VIH-1 (2012)
ABSTRACT: The clinical course of infection with human immunodeficiency virus type-1 (HIV-1) is a variable and complex process that depends on viral and host components. In the majority of infected individuals, the immune response is generated from the initial phases of infection, achieving the control of the viral replication through innate effector mechanisms, neutralizing specific antibodies and particularly through cytotoxic CD8+T cell activity. Despite the generation of these specific cellular and humoral responses, it becomes ineffective in chronic stages of infection because of changes in viral peptide targets, the low fidelity of the reverse transcriptase and the immune pressure. During the activation of CD8+ T cells, the signal delivered by the viral peptide presented in the context of the class I major histocompatibility complex (MHC-I) molecules, is essential. Correlation studies between the MHC-I and the resistance/ susceptibility (R/S) to HIV infection have focused on four aspects, namely: 1) the expression of specific alleles; 4) the degree of homozygosity/heterozygosity; 3) the degree of exposure to different alloantigens; 4) the relation with KIR receptors. In this review, we focus on resistance/susceptibility to HIV-1 infection, particularly related to the MHC, hoping to have a better understanding of this phenomenon that may allow the development of novel therapeutic intervention tools.